TIDAL GROUNDWATER LEVEL FLUCTUATIONS IN L-SHAPED LEAKY COASTAL AQUIFER SYSTEM - Li H.; Jiao J.J. (My University, 2002)
This paper presents an analytical solution to describe tidal groundwater level fluctuations in a coastal leaky aquifer system bounded by water-land boundaries that form a right angle (referred to as L-shaped coastlines). The system consists of an unconfined aquifer, a confined aquifer and a leaky layer between them. Previously published analytical solutions that discuss only single aquifer constitute a special case of the new solution when the permeability of leaky layer approaches zero. A simple approximate solution without integral is presented. Error analysis and hypothetical example show that the approximate solution has adequate accuracy for both groundwater level prediction and parameter estimation for an L-shaped leaky aquifer system.
Keywords: PERIODIC GROUNDWATER FLOW; ANALYTICAL SOLUTION; COASTAL AQUIFER SYSTEM; SEA TIDE; L-SHAPED COASTLINE; LEAKY AQUIFER